IMPLEMENTATION OF A CONTEXTUAL APPROACH IN IMPROVING THE ABILITY TO WRITE DESCRIPTION OF STUDENTS OF CLASS X SMA NEGERI 1 MANIAMOLO 2020/2021 SCHOOL YEAR - Dakhi, Nituhoizisokhi (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2020)
ABSTRACK This research is motivated by the students' ability in writing and understanding descriptive text is still lacking. This is because students do not really understand what they have to write in order to produce a description essay. To improve the description writing skills of SMA Negeri 1 Maniamolo students, the authors apply a learning model through a contextual approach with the aim of improving descriptive writing skills in students. This research was carried out at SMA Negeri 1 Maniamolo with the research subjects of class X IPA 1 totaling 17 people. The form of this research is classroom action research (CAR). Based on the results of the study it can be concluded that, (1) the average is 68.00 and in Cycle II there is an increase to 70.24 and from the achievement of KKM 58.82% to 70.59%. In Cycle III, there was an increase in description writing skills from the average of cycle II, namely 70.24 to 73.88 and the KKM achievement from 70.59% to 88.24%. Therefore, it can be concluded that based on the results of the study, it can be concluded that, there is an increase in description writing skills after carrying out class actions through a contextual approach. This can be shown by increasing the skills to write descriptions before and after the action.